PENGGUNAAN KONJUNGSI DALAM BAHASA TULIS DAN LISAN OLEH SISWA KELAS LIMA SEKOLAH DASAR BAKI PANDEYAN 01 SUKOHARJO - Nugraha, Oktavian Aditya; Ngalim, Abdul; Nasucha, Yakub (Jurnal Penelitian Humaniora, 2015)
This research deals with the use of conjunction in Indonesian language by the fifth graders of Baki Pandeyan 01 Elementary School of Sukoharjo. The objective of this study is three folds: (1) to describe conjunction used in spoken Indonesian Language; (2) to describe conjunction used in written Indonesian Language; (3) to describe errors in using conjunction both in written and spoken Indonesian. This research isÂ categorized into descriptive qualitative research. The object of this research is the conjunction used in spoken and written of Indonesian language of the fifth grade.The data of the research was the conjunction used in Indonesian Language of the fifth grade students which were collected through writing and retelling the story. The technique of data collection was done by using tapping technique continued with scrutinize ability involvement technique, recording technique, and noticing technique. The technique of data analysis used intralingual match because it connects and compares the language itself. The result of the study showed that conjunction of spoken Indonesian language of subordinative reached 182, coordinative reached 64, and inter-sentences reached 3. The using of subordinative conjunction in written Indonesian language reached 104, and 49 for coordinative cinjunction. The conjunction often used by the fifth grade studens is dan. Conjuntion error often occurred in the use of words dan, tetapi, lalu, sedangkan which were used as the preposition, the wrong spelling of yg and /. This research also revealed that the characteristics of subordinative conjunction are as follows: (1) Connecting two points which equally important, (2) Connecting words or prhases which are equal, (3) It used in the compound sentence. Then, the characteristics of coordinative conjunction are (1) Connecting two or more sentences which the same syntactic status, (2) Forming the subordinative clause, (3) Used in the complex sentences. The characteristics of inter-clause conjunction are (1) Connecting one sentence to the others, (2) Combining two sentences.